Innovative activity of the agricultural organizations of the Bryansk region - L. V. Lebed'ko; T. A. Kazimirova (Путеводитель предпринимателя)
Questions of innovative activity of the agricultural organizations are considered. The factors influencing the level of innovative development of the agricultural organizations of the region are defined. The directions of innovative development are defined.